The Existence of Multiple Solutions for Nonhomogeneous Kirchhoff Type Equations in - Qi Zhang; Xiaoli Zhu (Abstract and Applied Analysis)
We are concerned with the existence of multiple solutions to the nonhomogeneous Kirchhoff type equation where are positive constants, , we can find a constant such that for all the equation has at least two radial solutions provided .